Gender Responsive Climate Change Adaptation and Mitigation Analysis through Flamboyan Climate Group in Tangerang City - Utami, Wahyu Kartiko; Indriyany, Ika Arinia (International Journal of Demos (IJD), 2024)
AbstractThe issue of gender equality is still not a priority in the government's climate change adaptation and mitigation efforts, even though climate change indirectly interacts with conditions of gender inequality and produces impacts that can be detrimental to women. The climate village programme, as one of the government's efforts to overcome climate change, is a programme that cannot be separated from gender issues. The aim of this research is to analyse climate change adaptation and mitigation efforts through the climate village programme and examine the presence of women in the programme. Using a case study approach, researchers analysed the efforts made by the Flamboyan group in overcoming climate change in Tangerang City. Through the climate village programme, the Flamboyan group succeeded in getting an award from the local government for its efforts in climate change even though it was only formed in 2022. The results of the research show that before the climate group was formed by the government, this group headed and dominated by women had independently fought for climate change since 2012 in various ways, starting from planting plants in people's yards, waste banks, clean and healthy lifestyles (PHBS) and so on. These efforts were carried out independently for a long time and consistently before finally being formed as a climate group by government in 2022. Therefore, even though it was only formed in 2022, this group managed to receive various awards from the government in 2023 for its efforts in climate change. This group also proves that women can not only be present in domestic affairs, but also public affairs and succeed in bringing change to their environment. The impact on the economy, social and environment has been felt by local groups and communities.Keywords: Climate Village Programme, Climate Change, Adaptation, MitigationÂ AbstrakIsu kesetaraan gender masih belum menjadi prioritas dalam upaya adaptasi dan mitigasi perubahan iklim yang dilakukan pemerintah, padahal perubahan iklim secara tidak langsung berinteraksi dengan kondisi ketidaksetaraan gender dan menghasilkan dampak yang dapat merugikan perempuan. Program kampung iklim sebagai salah satu upaya pemerintah dalam mengatasi perubahan iklim menjadi salah satu program yang tidak lepas akan permasalahan gender. Tujuan dari penelitian ini adalah untuk menganalisis upaya adaptasi dan mitigasi perubahan iklim melalui program kampung proklim serta mengkaji kehadiran perempuan dalam program tersebut. Dengan menggunakan pendekatan studi kasus, peneliti menganalisis bagaimana upaya yang dilakukan oleh kelompok proklim Flamboyan dalam mengatasi perubahan iklim di Kota Tangerang. Melalui program kampung proklim, kelompok proklim Flamboyan berhasil mendapatkan penghargaan dari pemerintah daerah atas upayanya dalam perubahan iklim meskipun baru terbentuk di tahun 2022. Hasil penelitian menunjukan bahwa sebelum dibentuk kelompok proklim oleh pemerintah, kelompok yang di ketuai dan didominasi oleh perempuan ini telah secara mandiri memperjuangkan perubahan iklim sejak tahun 2012 dengan berbagai cara, mulai dari penanaman tanaman dipekarangan rumah warga, bank sampah, pola hidup bersih dan sehat (phbs) dan lain sebagainya. Upaya-upaya ini dilakukan secara swadaya untuk waktu yang lama dan konsisten sebelum akhirnya dibentuk sebagai kelompok poklim di tahun 2022. Oleh sebab itu, meskipun baru terbentuk 2022 namun kelompok ini berhasil mendapatkan berbagai penghargaan dari pemerintah di tahun 2023 atas upayanya dalam perubahan iklim. Kelompok ini juga membuktikan bahwa perempuan tidak hanya bisa hadir di urusan domestik, namun juga urusan publik dan berhasil membawa perubahan pada lingkunganya. Dampak terhadap ekonomi, sosial dan lingkungan telah dirasakan oleh kelompok serta masyarakat sekitar.Kata kunci: Kampung Iklim, Perubahan Iklim, Mitigasi, Adaptasi